2013
DOI: 10.3109/21556660.2013.818544
|View full text |Cite
|
Sign up to set email alerts
|

In vitroevaluation of the effects of 4-aminopyridine on cytochrome P450 enzymes

Abstract: BackgroundDalfampridine extended release tablets (dalfampridine-ER, known as prolonged-, modified, or sustained-release fampridine tablets in some countries) are approved for the improvement of walking in patients with multiple sclerosis (MS). Dalfampridine-ER is an extended release formulation of 4-aminopyridine (4-AP). Dalfampridine-ER is incorporated into MS management strategies that may include disease-modifying and symptomatic therapies. Since several symptomatic therapies are partially or fully metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…Based on the assumption that CYP1A2 exists in human choroid plexus epithelial cells, it is possible that methamphetamine also activates CYP1A2 in humans and increases caffeine metabolism, resulting in differences in caffeine concentrations between blood and CSF. However, another study reported that 4-AP, which was used as an alternative to stimulants, neither inhibited nor induced CYP1A2 [36]. In the culture experiments of this study, the inhibition of caffeine transfer to the CSF in the BCSFB was stronger when 4-AP was simultaneously added instead of stimulants, suggesting that the inhibition of caffeine transfer was caused by triggers other than metabolic enzyme activity.…”
Section: Discussioncontrasting
confidence: 60%
“…Based on the assumption that CYP1A2 exists in human choroid plexus epithelial cells, it is possible that methamphetamine also activates CYP1A2 in humans and increases caffeine metabolism, resulting in differences in caffeine concentrations between blood and CSF. However, another study reported that 4-AP, which was used as an alternative to stimulants, neither inhibited nor induced CYP1A2 [36]. In the culture experiments of this study, the inhibition of caffeine transfer to the CSF in the BCSFB was stronger when 4-AP was simultaneously added instead of stimulants, suggesting that the inhibition of caffeine transfer was caused by triggers other than metabolic enzyme activity.…”
Section: Discussioncontrasting
confidence: 60%
“…There is limited metabolism of 4-AP in humans with ~90% excreted unchanged in the urine. However, 4-AP has been shown to inhibit CYP2E1 with an IC50 value of 125 μM (Caggiano and Blight 2013). Zebrafish have two homologous P450 enzymes, Cyp2y3 and Cyp2p6 (Tsedensodnom et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetics of 4‐AP and its extended‐release formulation have been well characterized . The drug exhibits dose proportionality, and excretion is through renal elimination primarily as unchanged drug (≥90%), with a low likelihood of drug–drug interactions mediated through hepatic cytochrome P450 metabolic pathways . However, oral administration of immediate‐release formulations results in rapid attainment of maximum plasma concentration ( T max : approximately 1 h), and a short elimination half‐life ( t 1/2 : approximately 3.5 h) .…”
Section: Clinical Development Of Dalfampridine‐ermentioning
confidence: 99%